Making Sense of Serotonin Through Spike Frequency Adaptation - Harkin, Emerson (Université d'Ottawa / University of Ottawa, 2023)
What does serotonin do? Just as the diffuse axonal arbours of midbrain serotonin neurons touch nearly every corner of the forebrain, so too is this ancient neuromodulator involved in nearly every aspect of learning and behaviour. The role of serotonin in reward processing has received increasing attention in recent years, but there is little agreement about how the perplexing responses of serotonin neurons to emotionally salient stimuli should be interpreted, and essentially nothing is known about how they arise. Here I approach these two aspects of serotonergic function in reverse order. In the first part of this thesis, I construct an experimentally-constrained spiking neural network model of the dorsal raphe nucleus (DRN), the main source of forebrain serotonergic input, and characterize its signal processing features. I show that potent spike-frequency adaptation deeply shapes DRN output while other aspects of its physiology are relatively less important. Overall, this part of my work suggests that in vivo serotonergic activity patterns arise from a temporal-derivative-like computation. But the temporal derivative of what? In the second part, I consider the possibility that the DRN is driven by an input that represents cumulative future reward, a quantity called state value in reinforcement learning theory. The resulting model reproduces established tuning features of serotonin neurons, including phasic activation by reward predicting cues and punishments, reward-specific surprise tuning, and tonic modulation by reward and punishment context. Because these features are the basis of many and varied existing serotonergic theories, these results show that my theory, which I call value prediction, provides a unifying perspective on serotonergic function. Finally, in an empirical test of the theory, I re-analyze data from an in vivo trace conditioning experiment and find that value prediction accounts for the firing rates of serotonin neurons to a precision ≪0.1 Hz, outperforming previous models by a large margin. Here I establish serotonin as a new neural substrate of prediction and reward, a significant step towards understanding the role of serotonin signalling in the brain.
Keywords: neuroscience; serotonin; reinforcement learning; neural coding